'Better Breeds?' The Colonial State, Africans and the Cattle Quality Clause in Southern Rhodesia, c.1912–1930. Issue 2 (3rd March 2016) - Mwatwara, Wesley; Swart, Sandra
Abstract : Colonial officials, veterinarians and animal scientists in tropical Africa managed 'native' livestock whose physical and behavioural characteristics, preferred food, and disease resistance were understood to be very different from the corresponding animals of their homelands. Furthermore, they were faced with unfamiliar relationships and management patterns between indigenous humans and their domestic animals. However, existing scholarship on the development of the agricultural economy and veterinary medicine in Southern Rhodesia suffers from a preoccupation with the so-called 'cattle complex' theory and the proletarianisation of Africans, and has tended to focus largely on the role of the state in agricultural development. Thus, this article covers a neglected aspect of settler attempts to introduce exotic cattle breeds to Africans, as a perceived panacea to overstocking, and as foundation stock intended to 'revolutionise' the African cattle economy. We argue that the way these colonial 'experts' and African livestock owners related to each other – and their animals – under these shifting circumstances expose key aspects of the colonial encounter.